B cells participate in tolerance and autoimmunity through cytokine production. (February 2014) - Luu, Van Phi; Vazquez, Monica I.; Zlotnik, Albert
Abstract In the 1950s, the discovery of autoantibodies produced by B cells seemed to provide a compelling mechanism underlying autoimmune diseases. The discovery of T regulatory cells and other T helper cell subsets shifted the field back towards a T cell central view. The success of rituxan, a chimeric mAb targeting CD20 on B cells, in the treatment of rheumatoid arthritis forced a review of the role of B cells in autoimmunity. Rituxan was first developed to treat lymphomas, and it also proved effective in treating rheumatoid arthritis, a disease not previously associated with B cells. One of the side effects of rituxan is a pronounced depletion of peripheral blood B cells, an effect that seemed to correlate with effectiveness in preclinical and clinical models of autoimmune diseases. B cell depletion was also shown to affect T cell populations, suggesting an antibody-independent mechanism through which B cells influenced rheumatic disease. Most recently, the identification of cytokine producing B cells (B regulatory and B effector cells) that modulate tolerance has added to our understanding of human health and disease and the mechanisms that break tolerance, as the B cell cytokine network produced by B cell subsets were shown to influence T cell numbers, as well as the polarization of T cell subsets (Tregs/Th1/Th2). Therefore, B cells have once again taken the center stage in tolerance and autoimmunity. Here, we review the role of B cells in autoimmunity, mainly through their ability to produce cytokines.